Parent perceptions and decision making about treatments for epilepsy: a qualitative evidence synthesis. Issue 1 (31st January 2023) - Uhl, Stacey; Konnyu, Kristin; Wilson, Renee; Adam, Gaelen; Robinson, Karen A; Viswanathan, Meera
Abstract : Objectives: Epilepsy treatment decision making is complex and understanding what informs caregiver decision making about treatment for childhood epilepsy is crucial to better support caregivers and their children. We synthesised evidence on caregivers' perspectives and experiences of treatments for childhood epilepsy. Design: Systematic review of qualitative studies using a best-fit framework and Grading of Recommendations Assessment, Development and Evaluation Confidence in the Evidence from Reviews of Qualitative Research (GRADE-CERQual) approach. Data sources: Searched Embase, PubMed, CINAHL, PsycINFO, SocINDEX and Web of Science from 1 January 1999 to 19 August 2021. Eligibility criteria: We included qualitative studies examining caregiver's perspectives on antiseizure medication, diet or surgical treatments for childhood epilepsy. We excluded studies not reported in English. Data extraction and synthesis: We extracted qualitative evidence into 1 of 14 domains defined by the Theoretical Domains Framework (TDF). One reviewer extracted study data and methodological characteristics, and two reviewers extracted qualitative findings. The team verified all extractions. We identified themes within TDF domains and synthesised summary statements of these themes. We assessed our confidence in our summary statements using GRADE-CERQual. Results: We identified five studies (in six reports) of good methodological quality focused on parent perceptions of neurosurgery; we found limited indirect evidence on parents' perceptions of medications or diet. We identified themes within 6 of the 14 TDF domains relevant to treatment decisions: knowledge, emotion; social/professional role and identity; social influence; beliefs about consequences; and environmental context and resources. Conclusions: Parents of children with epilepsy navigate a complex process to decide whether to have their child undergo surgery. Educational resources, peer support and patient navigators may help support parents through this process. More qualitative studies are needed on non-surgical treatments for epilepsy and among caregivers from different cultural and socioeconomic backgrounds to fully understand the diversity of perspectives that informs treatment decision making.